Seroprevalence of cattle brucellosis by rosebengal and ELISA tests in different villages of Duhok province: Lokman T. Omar, Nacheervan M. Ghaffar , Alind M. Amen ,Mohammed A.Ahmmed - Omar, Lokman T. (The Iraqi Journal of Veterinary Medicine, 2011)
The current study conducted in the Duhok province villages, Kurdistan region of Iraq during the period between September-December 2008, fulfilled by using Rosebengal and ELISA tests cattle of different sex and age were used comparing between these two tests and to determine the prevalence rate by both tests. A total number of 360 serum samples were collected (294 females, 66 males). The infected rate by RBT was 6.38% and by ELISA were 0.83%. According to the different animal ages and sex group showed that the infection rates were 5.4% and 12.1% in females and males, respectively. Cattle in age group 1-3 years and more than 4 years were showed that an infection rates were 3.8% and 11.8% respectively.